Ultrasonic assisted extraction and gas chromatography-tandem mass spectroscopy (GC-MS/MS) analysis of extracts from four cassia species - Jibril, Saidu (Tanjong Malim, 2020)
Ultrasonic assisted extraction and gas chromatography-tandem mass spectroscopy (GC-MS/MS) analysis of extracts from four cassia species by Jibril, Saidu